2018
DOI: 10.1111/pcn.12680
|View full text |Cite
|
Sign up to set email alerts
|

Increase of frontal cerebral blood volume during transcranial magnetic stimulation in depression is related to treatment effectiveness: A pilot study with near‐infrared spectroscopy

Abstract: These results suggest that the maintenance of frontal activation during stimulation in the course of TMS series is related to the effectiveness in the treatment of depression. Measurement of fHbC during stimulation is informative in the clinical use of TMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 26 publications
1
18
1
Order By: Relevance
“…However, this work establishes a precedent for functional targeting of TMS therapy using fNIRS-measured activity during tasks which have been identified as affected in a given disorder. Together with the recently published work by Shinba et al (2018), these studies make a compelling case that the ability or inability of excitatory rTMS to evoke hemodynamic activity may serve to inform clinical status and predict treatment response to TMS therapies.…”
Section: Effects Of Rtms Stimulation On Task-evoked Fnirs Activitymentioning
confidence: 84%
See 1 more Smart Citation
“…However, this work establishes a precedent for functional targeting of TMS therapy using fNIRS-measured activity during tasks which have been identified as affected in a given disorder. Together with the recently published work by Shinba et al (2018), these studies make a compelling case that the ability or inability of excitatory rTMS to evoke hemodynamic activity may serve to inform clinical status and predict treatment response to TMS therapies.…”
Section: Effects Of Rtms Stimulation On Task-evoked Fnirs Activitymentioning
confidence: 84%
“…Most recently, a clinical pilot study conducted by Shinba et al (2018), reported significant increases in midline [HbO] during 10 Hz rTMS stimulation at 120%RMT to the left-DLPFC (5.5 cm anterior to M1) for treatment of drug-resistant individuals with MDD. Over the course of a 6-week treatment regime, the authors observed that the continued presence of [HbO] increase in response to stimulation was associated with clinical improvement as described by the Montgomery-Asberg Depression Rating Scale (MARDRS).…”
Section: Effects Of Tms Stimulation On Fnirs Measures At Restmentioning
confidence: 99%
“…Their discoveries suggested that NIRS signals would be useful in evaluating social functioning in patients afflicted by late-onset depression (prior to treatment) and predicting the improvement in their social functioning after treatment. Furthermore, fNIRS can be used to predict the treatment response of not only antidepressants but also other novel treatments, such as neurostimulation (50,85,89), music therapy (49), and animal-assisted therapy (83).…”
Section: Use Of Fnirs To Monitor Treatment Responsementioning
confidence: 99%
“…Two recent meta-analyses collecting data from eight RCTs each one, (263 patients) [132] and (249 patients) [133], show major evidence for the beneficial effect of this form of rTMS in the treatment of MDD. These studies conclude that LF-rTMS (1 Hz) to the right DLPFC provides clinically meaningful benefits that are comparable to those of standard antidepressants and HF-rTMS [118] with fewer side effects [133].…”
Section: Low Frequency Rtms Versus High Frequency Rtmsmentioning
confidence: 72%
“…A later study showed that changes in frontal cerebral blood volume, measured as frontal hemoglobin concentration during TMS, are correlated with clinical outcomes of treatment [118].…”
Section: Dr Isaac Túnezmentioning
confidence: 99%